Analysis of Reading Comprehension to Solve Problems on "Descriptive Task" of Madrasah Ibtidaiyah Students - Qowiyudin, Agus; Salma, Hulliyatus; Hidayati, Rina (Puitika, 2024)
Abstract:Â This study was conducted to determine the reading comprehension ability and text problem solving ability of fifth grade students of MINU Nurul Huda. This research method used qualitative methodology. The principal, fifth grade teacher, and fifth grade students became the four subjects of this study. Data collection methods were carried out by means of interviews, observation, and documentation. Data analysis in this study was carried out using the interactive model data analysis technique, which includes data reduction, data presentation, inference, and validation steps. Source triangulation was also used to ensure the validity of the data in this study. The findings in this study show that all fifth grade students are proficient in reading and understanding reading texts, some students are able to understand the text after reading it, and fifth grade students are also proficient in writing. To understand a reading, the first thing students must do is read the text, understand the content of the text, and also be able to interpret the meaning of the text, on average they already have the ability to draw conclusions from a reading. Only a few of the students scored below the required score on the text test.